Metformin exerts glucose-lowering action in high-fat fed mice via attenuating endotoxemia and enhancing insulin signaling - Zhou Zi-yu; Ren Li-wei; Zhan Ping; Yang Han-yan; Chai Dan-dan; Yu Zhi-wen (Acta Pharmacologica Sinica, 2017)
Aim: Accumulating evidence shows that lipopolysaccharides (LPS) derived from gut gram-negative bacteria can be absorbed, leading to endotoxemia that triggers systemic inflammation and insulin resistance. In this study we examined whether metformin attenuated endotoxemia, thus improving insulin signaling in high-fat diet fed mice. Methods: Mice were fed a high-fat diet for 18 weeks to induce insulin resistance. One group of the mice was treated with oral metformin (100 mg·kg−1·d−1) for 4 weeks. Another group was treated with LPS (50 μg·kg−1·d−1, sc) for 5 days followed by the oral metformin for 10 d. Other two groups received a combination of antibiotics for 7 d or a combination of antibiotics for 7 d followed by the oral metformin for 4 weeks, respectively. Glucose metabolism and insulin signaling in liver and muscle were evaluated, the abundance of gut bacteria, gut permeability and serum LPS levels were measured. Results: In high-fat fed mice, metformin restored the tight junction protein occludin-1 levels in gut, reversed the elevated gut permeability and serum LPS levels, and increased the abundance of beneficial bacteria Lactobacillus and Akkermansia muciniphila. Metformin also increased PKB Ser473 and AMPK T172 phosphorylation, decreased MDA contents and redox-sensitive PTEN protein levels, activated the anti-oxidative Nrf2 system, and increased IκBα in liver and muscle of the mice. Treatment with exogenous LPS abolished the beneficial effects of metformin on glucose metabolism, insulin signaling and oxidative stress in liver and muscle of the mice. Treatment with antibiotics alone produced similar effects as metformin did. Furthermore, the beneficial effects of antibiotics were addictive to those of metformin. Conclusion: Metformin administration attenuates endotoxemia and enhances insulin sig